Assessment of Latvian renewable energy strategy - Botnaru, Diana (Riga Graduate School of Law, 2018)
The thesis has the major objective of an in-depth analysis of EU renewable energy sector with a closer look to Latvian, Lithuanian, Estonian legislation concerning that matter, in order to reveal the inconsistencies in Latvian renewable energy strategy and its legislative framework and propose recommendations for a more sustainable development.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law; Renewable energy; Baltic states